The Effect of Surface Finish by Varying Machining Strategies of Five-Axis Flank Milling for Curvy Angled Convex Profile - Sundi, S. A.; Izamshah, R.; Kasim, M.S.; Raffay, M.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The main aim of this research is to identify the best machining strategy on the five-axis flank machining curvy angled shapes using various machining approaches or strategies offered by CATIA V5 software. In machining of curvy angled shapes, the most important factor is to obtain the exact shape or machined part in certain acceptable tolerance with good surface finish. Hence, applying the right and the best machining strategy in Computer Aided Manufacturing (CAM) process is the most vital phase. The machining strategies that have been applied were Tanto Fan, Combin Tanto and Combin Parelm. In this study, only convex shape is analyzed throughout the study. Each of every machining part has been gone through a thorough analysis of surface finish by using Mitotuyo Surf-tester to determine the effect of the surface finish. Meanwhile, the parts chosen to be machined was modified aero-structural component part using the same aerospace standard material, Aluminum A6063. Based on the analysis carried out, the best machining strategy for the sample chosen part was Combin Parelm according to the mean Ra values. Factors contributed to the results obtained are further discussed in this paper.